2021
DOI: 10.1016/j.ensci.2020.100299
|View full text |Cite
|
Sign up to set email alerts
|

A first presentation of multiple sclerosis with concurrent COVID-19 infection

Abstract: Infection from SARS-CoV-2 virus has developed into a worldwide pandemic. Potential neurological complications include meningitis, encephalitis, Guillain-Barre syndrome, cerebrovascular disease, seizures, and demyelinating disease. In this paper, we describe a case of newly diagnosed multiple sclerosis co-occurring with active COVID-19 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 19 publications
0
39
0
3
Order By: Relevance
“…However, to date, few reports concerning the development of MSassociated demyelination in COVID-19 patients shortly following the infection have been published (Palao et al, 2020, Domingues et al, 2020, Moore et al, 2021 (summarized in Table-3). Kataria et al have reported three RRMS patients who experienced worsening clinical symptoms following the COVID-19 contraction.…”
Section: Current Knowledge On Sars-cov-2 and Ms-associated Demyelinationmentioning
confidence: 99%
“…However, to date, few reports concerning the development of MSassociated demyelination in COVID-19 patients shortly following the infection have been published (Palao et al, 2020, Domingues et al, 2020, Moore et al, 2021 (summarized in Table-3). Kataria et al have reported three RRMS patients who experienced worsening clinical symptoms following the COVID-19 contraction.…”
Section: Current Knowledge On Sars-cov-2 and Ms-associated Demyelinationmentioning
confidence: 99%
“…We report a case of CNS demyelination following SARS-CoV-2 infection, that fulfilled the revised 2017 McDonald diagnostic criteria for MS. To our knowledge, this is the second published case report ( Moore et al, 2021 Mar 1 ), and the first from Middle East and North Africa (MENA) region. Both cases presented with ataxia, showed positive OCBs in CSF, and multiple demyelinating lesions in the brain MRI, with normal spine.…”
Section: Discussionmentioning
confidence: 82%
“…Both cases report the presence of autoantibodies with known association to SLE, including anti-La, anti-CCP, anti-SSA/Ro [72], ANA and anti-dsDNA antibodies [73]. Some patients have also been found to meet the criteria for diagnosis of MS following COVID-19 [74][75][76]. In each of these cases, markers of autoimmunity (e.g., ANA, anti-La) as well as autoantibodies to neuronal targets aquaporin-4 and myelin oligodendrocyte glycoprotein were negative, suggesting that autoantibodies may not always be involved in the aetiologies of these COVID-19 related autoimmune-like conditions.…”
Section: Systemic Lupus Erythematosus Multiple Sclerosis and Systemic Rheumatoid Diseasementioning
confidence: 99%